Research on Dynamic Pricing and Long-Term Profit of Companies under Influence of Word of Mouth - Feiyan Han; Yunchao Guo; Haofei Yu; Bo Li (Journal of Theoretical and Applied Electronic Commerce Research, 2024)
Word of mouth (WOM) is crucial in customers’ purchasing decisions and affects companies’ long-term profits. This study examines the long-term trends in companies’ dynamic pricing and profits by using the Hamiltonian function method and dynamic simulation to construct a dynamic equation. It takes into account the intensity of word of mouth faced by companies and analyzes the level of publicity and consumers’ predictions of product quality. In this paper, we also discuss the interactive processes between WOM and advertising levels, the two most prominent market factors, and their ultimate impact on companies. The experimental results show that elevated levels of external advertising can potentially prompt companies to establish higher product pricing strategies, particularly in scenarios where the intensity of word of mouth is pronounced. In the initial phases of market development, the saturation level of consumers within the market exerts a negligible influence on companies’ long-term profit margins. Conversely, the rate of natural attrition from consumers’ upper threshold of product quality expectations distinctly impacts companies’ profitability.